(untitled) (International Journal of Engineering and Computer Science, 2018)
Chip morphology is the remnant of the machining processes, providing to examine the quality of the machinability. The shape of the chip and its deformation rate identifying the severe of the processes outcomes like surface quality, tool life, required cutting forces and power. Especially plastic deformation in primary deformation zone makes the volume of the chip increase. The shear angle (φ), tool cutting edge approach angle (χ), and chip thickness (t) are the most influential parameters on the volumetric chip expansion factor (r1) in primary deformation zone. While tool cutting edge angle (χ) has a correlate proportional effect, shear angle (φ) and chip thickness (t) inversely proportional effect, on the volumetric chip expansion factor. According to getting the optimum volumetric chip expansion factor (r1), the lower tool cutting edge angle and feed rates, but higher shear angle must be selected. Rake angle (α) and cutting depth (a) have not remarkable effect on the volumetric chip expansion factor (r1), but rake angle only provides the sliding of the chip on the tool rake face.